2021
DOI: 10.3390/en14164946
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Eco-Apps in Encouraging Pro-Environmental Behavior of Young People Studying in Poland

Abstract: Nowadays, protection of the natural environment is the fundamental duty and challenge of humanity. Adverse environmental changes make it necessary to encourage behaviors that will reduce our negative impact. Due to the development of media, information reaches consumers through various channels. New media, including mobile applications, are becoming increasingly popular. Their potential impact on young consumers cannot be overestimated as young people are able to modify their attitudes, behaviors and habits mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…The following research questions were asked: In this study, the hypothesis was adopted that the statistical Polish consumer undertakes pro-environmental behavior because of its positive impact on the natural environment. The hypothesis was formulated on the basis of literature analysis, which shows that the statistical Polish consumer is a very conscious citizen and is aware of the importance of cleanliness of the environment and its impact on the global ecosystem of the planet [4,5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following research questions were asked: In this study, the hypothesis was adopted that the statistical Polish consumer undertakes pro-environmental behavior because of its positive impact on the natural environment. The hypothesis was formulated on the basis of literature analysis, which shows that the statistical Polish consumer is a very conscious citizen and is aware of the importance of cleanliness of the environment and its impact on the global ecosystem of the planet [4,5].…”
Section: Methodsmentioning
confidence: 99%
“…At this point, it is worth referring to Prospect Theory, which is considered a better model for understanding decision making than traditional expected utility theory in many fields [67]. Viewed in this light, environmentally friendly behaviors [4,5,68,69], in the long run, can bring various value-added benefits (e.g., health, clean air, etc.) to the decision-making process.…”
Section: A Structural Model Of Pro-ecological Behavior In Relation To...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, BSSs can be used as a health promotion and prevention tool. Some research works emphasize that BSSs provide a healthy lifestyle and a sustainable environment to the world as well as encourage pro-environmental behavior of people [34]. Sometimes city residents use BSSs and e-bikes as a means of transport for trips outside the urban area [35][36][37].…”
Section: Trip Records Of the Bssmentioning
confidence: 99%
“…Results from an online survey showed that gender, age and class standings had a positive correlation with environmentally friendly behavior. Balinska et al [17] tried to understand the role of eco-friendly mobile applications on the environmentally friendly behavior of undergraduates in Poland. The results showed that applications widely promoted in traditional media gained stronger recognition, while statistically, females understood the usefulness of these applications better then males.…”
Section: Literature Reviewmentioning
confidence: 99%